(untitled) (Journal of Open Law, Technology & Society, 2018)
The Git revision control system does not enforce correctness of data but instead is reliant on correct inputs for correct outcomes. Git records potential authorship rather than copyright ownership and this means that an additional process layer is needed to ensure fidelity and accuracy of data. The core implication is that the “git blame” tool does not show potential authorship with enough granularity to make clear decisions and additional review is required to determine potential authors of code contained in any Git repository.